The XTH Gene Family in Schima superba: Genome-Wide Identification, Expression Profiles, and Functional Interaction Network Analysis - Yang, Zhongyi; Zhang, Rui; Zhou, Zhichun (Frontiers in Plant Science, 2022)
Xyloglucan endotransglucosylase/hydrolase (XTH), belonging to glycoside hydrolase family 16, is one of the key enzymes in plant cell wall remodeling. Schima superba is an important timber and fireproof tree species in southern China. However, little is known about XTHs in S. superba. In the present study, a total of 34 SsuXTHs were obtained, which were classified into three subfamilies based on the phylogenetic relationship and unevenly distributed on 18 chromosomes. Furthermore, the intron–exon structure and conserved motif composition of them supported the classification and the members belonging to the same subfamily shared similar gene structures. Segmental and tandem duplication events did not lead to SsuXTH gene family expansion, and strong purifying selection pressures during evolution led to similar structure and function of SsuXTH gene family. The interaction network and cis-acting regulatory elements analysis revealed the SsuXTH expression might be regulated by multiple hormones, abiotic stresses and transcription factors. Finally, expression profiles and GO enrichment analysis showed most of the tandem repeat genes were mainly expressed in the phloem and xylem and they mainly participated in glycoside metabolic processes through the transfer and hydrolysis of xyloglucan in the cell wall and then regulated fiber elongation.